In vitro biological effects of pinewood sawdust and sugarcane bagasse-derived xylooligosaccharides on Lactobacillus biomass and antibacterial properties of its postbiotics on multidrug-resistant mastitogenic Staphylococcus aureus - Claudious Gufe; Tatenda Chijaka; Tinashe Muteveri; Peter Katsande; Benard Mbonjani; Prosper Jambwa (Cogent Food & Agriculture)
Xylooligosaccharides (XOS) produced from pinewood sawdust and sugarcane bagasse xylan using crude xylanase from the probiotic Bacillus licheniformis were used to evaluate their ability to stimulate the growth of Lactobacillus species, as well as their antibacterial activity against multidrug-resistant Staphylococcus aureus (MDR-SA) isolated from cows with recurrent mastitis. The ability of the two XOS products to stimulate probiotic growth was evaluated using selected Lactobacillus strains, while the antibacterial activity of the postbiotics against MDR-SA was determined using the agar well diffusion method. Most of the S. aureus isolates (75%) had a 90% antibiotic-resistant rate. The XOS products stimulated the growth of Lactobacillus species, with the probiotic cultures growing faster when sugarcane bagasse XOS was used as a carbon source compared to pinewood sawdust XOS. Lactobacillus plantarum has a higher specific growth rate than Lactobacillus acidophilus and Lactobacillus casei. Cell-free supernatants of probiotic bacteria grown in a medium containing XOS as the sole carbon source exhibited weak to strong antibacterial activity against MDR-SA, with L. plantarum supernatants from the two lignocellulosic biomasses showing the most inhibition, followed by L. acidophilus and L. casei. The study showed that XOS generated from xylan extracted from the two biomasses has the potential to promote the growth of beneficial Lactobacillus species and that XOS plus probiotic combinations are prospective antibacterial agents against mastitogenic MDR-SA strains.